An empirical analysis of organizational external factors on construction risk management - Adeleke, Adekunle Qudus; Bahaudin, Ahmad Yusni; Kamaruddeen, A. M.; Bamgbade, J.A.; Ali Khan, Muhammad Waris; Panda, Sitansu; Afolabi, Yakibi Ayodele (ExcelingTech Publishers, 2019)
Over the past years, construction risk management in projects execution is always associated with uncertainties because certain risk factors such as poor labour productivity, shortage of equipment, delay, cost overrun, time overrun are attributed to project delivery. These risk factors have been generating many research interests among the construction stakeholders and the policymakers, necessitating this present study. In addressing this issue, this study utilized Partial Least Squares- Structural Equation Modeling method to validate construction risk management (CRM) as a construct from the viewpoints of multi-national, local and national construction companies in Nigeria. Through a cross-sectional survey, data were collected from the construction companies with the use of a structured questionnaire. It was discovered that technology, political and economic factor have a significant influence on construction risk management (CRM) among the Nigerian construction companies. A substantial degree of convergent validity, discriminant validity and internal consistency reliability were also affirmed for each of these research constructs. It was also discovered that the indicators of organisational external factors dimensions (technology, political and economic factor) are important in evaluating these constructs for further exploration of the construction companies to enhance risk management practice in all stages of the project activities.